Practice and Thinking of Peer Assistance Class Mentorship System in Promoting Students’ Comprehensive Development (Journal of Global Humanities and Social Sciences, 2024)
In the current vocational education environment, the comprehensive development of students has become an important goal of education reform, which, in addition to the cultivation of professional skills, also emphasizes the cultivation of students’ ways of thinking, creative abilities and sense of social responsibility. Educational reforms in vocational colleges and universities have focused on building an open and diversified learning environment, encouraging students to develop their personal hobbies and social interaction skills while learning professional skills, as well as increasing investment in humanities, arts and science education to cultivate critical thinking and the ability to solve complex problems, so as to enable students to adapt to the fast-changing labor market while taking into account both their personal development and the needs of society. As a result, the peer-help classroom guidance system has emerged, which forms an effective educational and growth support system that enhances students’ social skills and shapes leadership and teamwork through the driving and tutoring of junior students by their senior counterparts. This paper analyzes the factors affecting the overall development of students in vocational colleges and universities, and then deduces the advantages of the peer-help class guide system, revealing the positive impact of the facts of the system on the overall development of students.